2021
DOI: 10.1016/j.lanwpc.2021.100262
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Liver Transplantation in Hong Kong and Singapore: A Modelling Study

Abstract: Background Liver transplantation (LT) activities during the COVID-19 pandemic have been curtailed in many countries. The impact of various policies restricting LT on outcomes of potential LT candidates is unclear. Methods We studied all patients on the nationwide LT waitlists in Hong Kong and Singapore between January 2016 and May 2020. We used continuous time Markov chains to model the effects of different scenarios and varying durations of disruption on LT candidates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“… Among patients with COVID-19 and chronic liver disease in the US National COVID Cohort Collaborative, the presence of cirrhosis was associated with an increased risk of mortality (adjusted HR 3.3) 129 . In the early phase of the COVID-19 pandemic, cirrhosis referrals, hospitalizations and clinic visits declined substantially, which might have contributed to lower quality of care, delayed presentation and loss of follow-up 95 , 96 , 130 , 131 . A global study conducted at 44 international centres determined that consultations, testing and treatment rates for hepatitis B virus and hepatitis C virus infection decreased substantially between January 2019 and December 2020, and this decrease was related to the COVID-19 pandemic 89 .…”
Section: Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“… Among patients with COVID-19 and chronic liver disease in the US National COVID Cohort Collaborative, the presence of cirrhosis was associated with an increased risk of mortality (adjusted HR 3.3) 129 . In the early phase of the COVID-19 pandemic, cirrhosis referrals, hospitalizations and clinic visits declined substantially, which might have contributed to lower quality of care, delayed presentation and loss of follow-up 95 , 96 , 130 , 131 . A global study conducted at 44 international centres determined that consultations, testing and treatment rates for hepatitis B virus and hepatitis C virus infection decreased substantially between January 2019 and December 2020, and this decrease was related to the COVID-19 pandemic 89 .…”
Section: Predictionsmentioning
confidence: 99%
“…In the early phase of the COVID-19 pandemic, cirrhosis referrals, hospitalizations and clinic visits declined substantially, which might have contributed to lower quality of care, delayed presentation and loss of follow-up 95 , 96 , 130 , 131 .…”
Section: Predictionsmentioning
confidence: 99%
“…Forty-four studies reported clinical outcomes such as mortality and morbidity. 2 4-6 10 12-17 20 21 23-37 39-46 49-52 [54][55][56][57] Fifteen studies reported public health goal outcomes (eg, delay in reaching disease elimination targets). 11 18 19 25 26 33 35 37 44 47 48 53 54 56 57 Seventeen articles reported humanistic outcomes (such as change in risky behaviour 2 5 12 14 16 20 21 23 24 29 35 41 43 49 50 52 and quality of life 28 ) and four articles 22 29 35 38 reported economic outcome (eg, financial loss).…”
Section: Effects Of Covid-19 Disruptions Modelledmentioning
confidence: 99%
“…The former was divided into 5 subgroups, including diagnosis of HCC in medical centres [16][17][18][19][20][21][22], activities of diagnostic centres and pathology laboratories [23][24][25], delay in diagnosis [18], screening method [26], and risk of HCC in patients with related alcohol-related hepatitis [27]. The latter was divided into 13 subgroups, including delaying or stopping treatment activities [18,19,22,[28][29][30], activities of medical centres [26,28,[31][32][33], modifying treatment methods [18,19,29,34], LT in patients with HCC [25,29,[35][36][37], visiting and consulting patients [18,19,22,25,26,29,33,38], hospitalization [29], performing treatment methods [19,25,29,33,…”
Section: Characteristics Of Included Studies and Quality Assessmentmentioning
confidence: 99%